INFORMED CONSENT DAN REKAM MEDIS DALAM TELEMEDICINE DI INDONESIA - Aidha Puteri Mustikasari (HUKUM PEMBANGUNAN EKONOMI, 2020)
AbstractHealth services continue to develop following the updates in information technology, one of  which is the use of telemedicine as a means of communicating between doctors and patients who experience long-distance consultation or treatment interactions. Not only to make it easier, but there are several new problems related to the delivery of informed consent, where any information related to disease diagnosis and treatment must be accepted, understood and approved by the patient. The recording of medical records has also experienced some turmoil because the data security system in Indonesia is not ready to allow the leakage of confidential information related to patients. Telemedicine is also not easy to do because there is no physical examination that can help doctors diagnose a disease, and it does not rule out that patients are not honest in providing information related to their condition. So this study focuses on how to deliver informed consent in the telemedicine process and the efforts that can be made to maintain the confidentiality of medical records. The government, the Indonesian Medical Association and the Medical Ethics Council are expected to support efforts to make telemedicine services in Indonesia safer and more orderly. AbstrakLayanan kesehatan terus berkembang mengikuti perkembangan teknologi informasi, salah  satunya adalah penggunaan telemedicine sebagai sara berhubungan antara dokter dengan pasien yang memberi kan pengalama konsultasi atau interaksi pengobatan jarak jauh. Tidak semata-mata mempermudah namun ada beberapa hal yang menjadi masalah baru yaitu terkait dengan penyampaian informed consent yang mana setiap informasi terkain dengan diagnose penyakit dan penangana harus dapat diterima, dimengerti dan disetujui oleh pasien. Pencatatan rekam medis juga mengalami guncngan karena belum siapnya sistem pengamanan data yang ada di Indonesia memungkinkan adanya kebocoran terhadap informasi rahasia terkait dengan pasien. Telemedicine juga tidak mudah untuk dilakukan pasalnya tidak adanyanya pemeriksaan fisik yang dapat membantu dokter dalam mendiagnosa suatu penyakit, serta tidak menutup kemungkinan bahwa pasien tidak jujur dalam memberikan informasi terkait dengan keadannya. Maka penelitian ini berfokus pada bagaimana cara penyampaian informed consent dalam proses telemedicine dan upaya yang dapat dilakukan untuk menjaga kerahasiaan rekam medik. Pemerintah, Ikatan Dokter Indonesia dan Majelis Kehormatan Etik Kedokteran diharapkan dapat mendukung upaya-upaya agar layanan telemedicine di Indonesia menjadi lebih aman dan tertata.